Potential for and impacts of mainstreaming diversification crops through institutional catering - André, Marine; Pujos, Lise; Martin, Guillaume (Frontiers in Sustainable Food Systems, 2024)
Introduction In France, land use is dominated by a narrow range of crops. As crop diversification is increasingly promoted to transform the food system, outlets for diversification crops need to be identified. We assess the scope for introducing diversification crops from farmers’ fields to canteen plates, and the agroecological, environmental, work-related and nutritional impacts of their introduction. Methods We focus on three diversification crops: chickpea, squash, and millet, to partly replace soft wheat, potato, and durum wheat, respectively. For each crop, we define three scenarios of low (1), medium (2) and high (3) integration into institutional catering on a national scale. We assess the scenarios against the amount of diversification cropland area needed and their expected impacts. Results Diversification crops can be developed through institutional catering. Taking the case of chickpea, in Scenario 1, chickpea flour is introduced in a cake served once every 20 days, replacing 30% of the soft wheat flour used. This amounts to 874 ha cropped. In Scenario 2, chickpea flour partly replaces wheat flour in all preparations, and 4,048 ha are required. In Scenario 3, raw chickpeas are also introduced into new recipes and 20,958 ha are needed. All three diversification crops support the establishment of agroecological cropping systems, with enhanced nutrient cycling in particular, and reduce their environmental footprint, notably by avoiding pesticide use. Diversification crops do not generate work constraints for farmers and cooks. However, they have a lower productivity per unit area than the reference crops, although they do improve several nutrition parameters such as fiber intake. Discussion We show for the first time that institutional catering provides a tangible outlet for developing diversification crops and improving the sustainability of agriculture. Our scenarios can support concerted actions between farmers, supply-chain actors, cooks and policy makers, as well as communication to eaters surrounding their impacts on agriculture.